2022
DOI: 10.3390/app122412708
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Performance of Foam Concrete Prepared from Decarburized Fly Ash

Abstract: Although the energy structure has been gradually enriched in recent years, China, as the world’s largest producer and consumer of coal, still accounts for more than 50% of resources. Therefore, in this paper, the high carbon fly ash raw ash (HCFARA) was mechanically activated, and the flotation was treated to obtain decarburized fly ash (DFA) with a loss on ignition of 1.18%, water demand ratio of 101% and strength activity coefficient of 74.5%. With the exception of for water demand ratio, the rest meet the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The addition of ash of more than 40% leads to a fairly strong loss of strength and a significant deterioration in other characteristics. In general, the use of fly ash in foam concrete is justified and, with the correct selection of the formulation, allows one to obtain composites with improved thermal insulation characteristics and lower density while maintaining an acceptable reduction in compressive strength, which is also confirmed by a number of the following studies [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 72%
“…The addition of ash of more than 40% leads to a fairly strong loss of strength and a significant deterioration in other characteristics. In general, the use of fly ash in foam concrete is justified and, with the correct selection of the formulation, allows one to obtain composites with improved thermal insulation characteristics and lower density while maintaining an acceptable reduction in compressive strength, which is also confirmed by a number of the following studies [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 72%
“…With that condition, a provision of mix design is necessary. Previous researchers such as Othman et al [36], Al Qubro et al [37], Ma et al [38] and Guo et al [39] successfully developed the mix design of foamed concrete with the inclusion of additive materials. Since this experimental study intends to use RHA and PMM, the mix design proposed by Abd Rahman et al [40] was found suitable and thus adopted.…”
Section: Designmentioning
confidence: 99%